Millet-based crop planting strategies in the Songhua River Region during the liaojin (907-1234 AD) dynasties: A case of the Luotong Mountain City site - Yang, Chun; Ban, Lin; Lv, Xiaohong; Li, Dong; Xu, Kun; Gao, Xiuhua; Wang, Chunxue (Frontiers in Plant Science, 2022)
Introduction Millet-based dryland agriculture is the traditional mode of agricultural cultivation in northern China and has been of great significance to the emergence and development of Chinese civilization. However, although they are both millet-based agricultural production methods, with various subtypes in different regions of northern China. In the Songhua River Region in northeast China, the ecological environment and abundant natural resources led to the slow development of agriculture, and it was only after the Liaojin Dynasties that a mature farming industry was formed. Material and Method We used the plant flotation instrument to flotation the soil samples unearthed in the Luotong Mountain City, a Liaojin period site in Songhua River Region, northeast China, and collected the charred plant seeds. Then observing them with the electron microscope, we identified and counted the plant seeds in this site. Result It was found that this region is still a millet-based crop utilization structure, and a total of 11 types of charred agricultural crop seeds were excavated from flotation at the Luotong Mountain City site. And the barnyard millet crops occupy a prominent advantage, with ubiquity of more than 91%. Discussion The ancestors of this region were still engaged in a millet-based agricultural strategy during this period, with a certain lag compared to the Central Plains’agricultural strategy where Triticeae crops had become dominant. In addition, the crop structure with the millet-based agriculture of the region is also somewhat different from that of the Central Plains. Through comparative studies of surrounding sites and reference to historical documents, it was found that this difference in crop structure is a phenomenon unique to the Songhua River Region and is related to the dietary habits of the local settled Jurchen nomads, who ate barnyard millet meal.